Corpus luteum score, a simple Doppler examination to prognose early pregnancies. (March 2021) - Blavier, Frederic; Faron, Gilles; Cools, Wilfried; Blockeel, Christophe; Santos-Ribeiro, Samuel; Done, Elisa; Ranisavljevic, Noemie; Rayssiguier, Romy; Fuchs, Florent; Gucciardo, Leonardo
Graphical abstract: Summarised predictions from CL score alone and combined to serum progesterone levels (μg/L) with: -First figure, up: description of corpus luteum scores -Table : distribution of evolving (viable) pregnancies, surgical removal of non-viable pregnancies, delay of non-surgical evacuations and complications according to corpus luteum scores 0, 1 and 2. -Second figure: predicted probability on evolutive pregnancies over amount of progesterone combined to CL Doppler score (0 red, 1 green and 2 blue) -Third figure: probability of long delay (>20 days) of non-surgical evacuation of non-viable pregnancy over amount progesterone and CL score (0 red, 1 green and 2 blue). Highlights: A score was established with Doppler prospective examinations of corpora lutea. All early pregnancies with a score/progesterone level were retrospectively reviewed. Outcomes were failed PUL, diagnosis, completion and complications of miscarriages. The corpus luteum score, alone, predicted significantly all these outcomes. These predictions improved adding serum progesterone levels and other factors. Abstract: Objectives: In early pregnancies, miscarriages and inconclusive ultrasound scans considering location and viability are very common. In several previous studies, serum progesterone levels predicted viability of pregnancy and, in recent ones, failed Pregnancies of Unknown Location (PUL), completion of miscarriage and complications. Corpus luteum, secreting progesterone in early pregnancy, was less studied. Some publications showed correlations between corpus luteum aspects and diagnosis of miscarriage but it was not evaluated for other outcomes in early pregnancy, such as failed PUL, completion of miscarriage or complications. We aimed to assess if Doppler examination of corpus luteum could also predict all these outcomes: failed PUL, diagnosis and completion of miscarriages and complications. Study design: A single operator prospectively described and/or collected pictures of Doppler signal in the wall of the corpus luteum at most consultations in our early pregnancy unit and established a three-level score. All suspected or confirmed non-viable pregnancies with this score or/and serum progesterone levels were registered retrospectively. With logistic regressions, AIC/BIC, likelihood ratios, ROC curves, Mann-Whitney and Fisher exact tests, we evaluated the ability of the score, alone, to predict failed PUL, diagnosis and completion of miscarriages and the complications, and, combined, to improve previously published predictions. Results: From 277 included pregnancies, 186 (67.1 %) miscarried. Of these, 159/186 (85.5 %) fully evacuated without surgery: 114/186 (61.3 %) within 20 days after the first diagnosis and 45/186 (24.2 %) after more than 20 days. Twenty-seven patients (14.5 %) underwent surgical evacuation, including ten complications, five haemorrhages and five suspected infections. Logistic regression correlated strongly the corpus luteum score with failed PUL (p < 0.0001) and miscarriages (p < 0.0001). Moreover, rates of complications and swift non-surgical completions of miscarriage were respectively 0 % and 92 % with scores of 0, versus 6 % and 44 % with scores of 1, versus 16 % and 0 % with scores of 2. Combined with serum progesterone levels, this score improved most predictions. Adding parity or history of miscarriage in predictive models even increased these performances. Conclusions: Corpus luteum score, alone, can predict failed PUL, diagnosis and completion of miscarriages and their complications. Combining this score with other factors (mainly serum progesterone levels) improves most predictions.